Formal Semantics in the Neurology Clinic: Atypical Understanding of Aspectual Coercion in ALS Patients - Baggio, Giosuè; Granello, Giulia; Verriello, Lorenzo; Eleopra, Roberto (Frontiers in Psychology, 2016)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease of the motor system with subtle adverse effects on cognition. It is still unclear whether ALS also affects language and semantics, and if so, what aspects and processes exactly. We investigated how ALS patients understand verb phrases modified by temporal preposition phrases, e.g., ‘To watch TV for half an hour’. Interpretation here requires operations such as aspectual coercion that add or delete elements from event structures, depending on temporal modifiers, and constraints on coercion, which make combinations with certain modifiers not viable. Using a theoretically-motivated experimental design, we observed that acceptance rates for aspectual coercion were abnormally high in ALS patients. The effect was largest for the more complex cases of coercion: not those that involve enrichment of event structures (‘To switch on the TV in half an hour’, where a number of failed attempts must be included in the interpretation) but those that, if applied, would result in deletion of event structure elements (‘To repair the TV for half an hour’). Our experimental results are consistent with a deficit of constraints on coercion, and not with impaired semantic processes or representations, in line with recent studies suggesting that verb semantics is largely spared in ALS.